Evaluasi Tebal Perkerasan Lentur Dengan Metode Analisa Komponen Dari Bina Marga 1987 Dan Metode Aashto 1993 Menggunakan Program Kenpave (Studi Kasus: Jalan Karangmojo-Semin Sta 0+000 sampai Sta 4+050) - Dinata, Doni Ikrar; Rahmawati, Anita; M, Dian Setiawan (Semesta Teknika, 2017)
In Indonesia, many roads have been damaged especially on flexible pavement design. There are caused by the high of traffic volume, extreme climate changes, the bad subgrade quality and the lack of quality of pavement material. The aim of this research is to analysis of the pavement quality of the road using KENPAVE program. Case study research is on Karangmojoâ Semin road,Â Sta. (0 + 000) to Sta. (4 + 050), Gunung Kidul,Â D.I Yogyakarta. The program can give the value of stress and strain on the road due to traffic load. The response ofÂ stress and strain caused by fatigue cracking and rutting from KENPAVE output with pavement thickness analysis using Bina Marga 1987method are 0,000408 and 0,00138, respectively and using AASHTO 1993 method the fatigue crackingand rutting are 0,000322 and 0,00134, respectively. The flexible pavement design using method of Bina Marga 1987 and AASHTO 1993 produce the amount of load repetition with a traffic load plan is greater than the number of repetition load plan, so the road will have possibilities ofÂ fatigue cracking and rutting damage before the design life reached.